2021
DOI: 10.1039/d0cs01084g
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal chemistry strategies for discovering antivirals effective against drug-resistant viruses

Abstract: This review summarizes current advances in medicinal chemistry aimed at the discovery of antiviral compounds specifically targeted against drug-resistant strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
69
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(69 citation statements)
references
References 247 publications
0
69
0
Order By: Relevance
“…However, just one antiviral drug is usually not enough for a safe cure with this type of infectious agent, due to the facile emergence of mutations, which may lead to strains resistant to the drug, as already well documented for other widespread viral infections, such as HIV, HCV, Ebola, etc. [16][17][18][19][20][21] and mentioned above to be the case of SARS-CoV-2 too. Thus, the development of novel specific and effective antiviral agents that target various coronavirus (or even host) proteins should continue in order to supplement the vaccine and MAb therapeutics with such small-molecule drugs.…”
Section: Coronavirusesmentioning
confidence: 84%
“…However, just one antiviral drug is usually not enough for a safe cure with this type of infectious agent, due to the facile emergence of mutations, which may lead to strains resistant to the drug, as already well documented for other widespread viral infections, such as HIV, HCV, Ebola, etc. [16][17][18][19][20][21] and mentioned above to be the case of SARS-CoV-2 too. Thus, the development of novel specific and effective antiviral agents that target various coronavirus (or even host) proteins should continue in order to supplement the vaccine and MAb therapeutics with such small-molecule drugs.…”
Section: Coronavirusesmentioning
confidence: 84%
“…For such reasons, the multiple targeting approach was initially considered mainly for multifactorial diseases such as cancer 6–8 , Alzheimer’s and other neurodegenerative diseases 9 , 10 , schizophrenia 11 , etc. However, more recently the approach was successfully extended to the discovery of antibiotics 12 and antiviral drugs 13 , proving that it may be a general one.…”
Section: Introductionmentioning
confidence: 99%
“…Outbreaks of diseases caused by coronaviruses SARS-CoV (2002–2004), MERS-CoV (2012, 2014, 2015), filovirus Ebola (2014–2015, 2018–2019), as well as the current pandemic caused by coronavirus SARS-CoV-2 (2019–to date), has stimulated extensive research on antiviral compounds [ 1 , 2 , 3 , 4 , 5 , 6 ] and has shown the importance of the availability of approved broad-spectrum antiviral drugs suitable for rapid repurposing or repositioning [ 7 , 8 , 9 , 10 , 11 , 12 ] to combat emerging threats. The need for such drugs was postulated in 2015 [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%